Current status of research on Aleurodicus dugesii (Hemiptera: Aleyrodidae) on dutch eggplant - KETUT AYU YULIADHI; LISTIHANI LISTIHANI; DEWA GEDE WIRYANGGA SELANGGA; I PUTU SUDIARTA; GUSTI NGURAH ALIT SUSANTA WIRYA; I GEDE RAI MAYA TEMAJA (Society for Indonesian Biodiversity, 2024)
Abstract. Yuliadhi KA, Listihani L, Selangga DGW, Sudiarta IP, Wirya GNAS, Temaja IGRM. 2024. Current status of research on Aleurodicus dugesii (Hemiptera: Aleyrodidae) on dutch eggplant. Biodiversitas 25: 2241-2248. Aleurodicus dugesii Cockerell whitefly is considered to be a polyphagous insect which can parasitise a wide variety of hosts. Horticultural crops are the commodity most dominantly attacked by A. dugesii. Information on population density, damage severity, and genetic diversity of A. dugesii in Indonesia is still limited. This research aimed to determine the population density, the damage severity, and the genetic variety of A. dugesii at an eggplant cultivating center in Kintamani District, Bangli, Bali. The research was conducted on 8 plantations in Kintamani District. The A. dugesii was identified through morphology and molecular method of Polymerase Chain Reaction (PCR). Aleurodicus dugesii egg placement characteristics are circular, following the wax path formed, and at the underside of the leaf, there would be soft, long wax filament resembling a beard produced during the nymph stage. The highest A. dugesii whitefly population in duct eggplant crops during nymph, pupae, and imago stages were 184.6, 131.3, and 152.2 individuals per leaf. In Kintamani District, the highest damage severity reached 62%. The highest nucleotide homology of A. dugesii DNA cytochrome oxidase subunit I (COI) was found in the same species from Indonesia and the US, with >97% resemblance. This research enriches the information about the widening A. dugesii distribution area in Indonesia.